Early Introduction of Emotions: CERIA Program to Develop Children's Emotional Intelligence with Storytelling Methods - Dyan Prastika, Netty; Rahayu, Diah; Purwanti, Silviana (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2025)
The early introduction of emotions is an important step in supporting children's psychological development. However, many young children still struggle to recognize and express their emotions appropriately. The lack of effective methods in emotional education within school environments remains a challenge that needs to be addressed. The community service program "CERIA" (Smart Emotion through Storytelling Method) is designed to help young children recognize and express various types of emotions in a healthy way through an interactive and educational storytelling approach. This program was implemented at Alifia Kindergarten, Samarinda, involving 33 children as participants. The methods used include reading emotion-themed storybooks, interactive discussions, and craft activities to strengthen the children’s understanding of the emotions introduced. Evaluation results showed an increase in the children's ability to recognize and express various emotions, as well as improved engagement in emotion-based activities. This program highlights the importance of storytelling-based approaches in supporting the emotional development of young children and can serve as an effective learning model in early childhood education. Pengenalan emosi sejak dini merupakan langkah penting dalam mendukung perkembangan psikologis anak-anak, namun masih banyak anak usia dini yang kesulitan mengenali dan mengekspresikan emosi mereka dengan tepat. Kurangnya metode yang efektif dalam pendidikan emosional di lingkungan sekolah menjadi tantangan yang perlu diatasi. Program pengabdian masyarakat "CERIA" (Cerdas Emosi Melalui Metode Bercerita) dirancang untuk membantu anak-anak usia dini mengenali dan mengekspresikan berbagai jenis emosi secara sehat melalui pendekatan storytelling yang interaktif dan edukatif. Program ini dilaksanakan di TK Alifia, Samarinda, dengan melibatkan 33 anak sebagai peserta. Metode yang digunakan meliputi pembacaan buku cerita bertema emosi, diskusi interaktif, serta aktivitas prakarya untuk memperkuat pemahaman anak terhadap emosi yang telah diperkenalkan. Hasil evaluasi menunjukkan adanya peningkatan pemahaman anak-anak dalam mengenali dan mengekspresikan berbagai jenis emosi, serta meningkatkan keterlibatan mereka dalam aktivitas berbasis emosi. Program ini menegaskan pentingnya pendekatan berbasis cerita dalam mendukung perkembangan emosional anak usia dini dan dapat menjadi model pembelajaran yang efektif dalam pendidikan anak.